AN EXAMINATON OF COLLABORATIVE STRATEGY READING ON STUDENTS’ READING COMPREHENSION IN RECOUNT TEXT - Nur Ali; Hanafi Wibowo (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2018)
This research aims to examine whether or not Collaborative Strategy Readingsignificantly affects on students’ reading comprehension. The research samples weretaken using cluster random sampling, with the total number of samples being 72students.The location of this research was SMK Pusaka 1 Jakarta. The research methodologyadopted was Quasi- Experimental methodby involving two groups, namely experimentgroup and control group, with the research design being randomized post-test only controlgroup design. To collect the data, the students were given objective test, numbering 30items. The research data were analyzed descriptively and inferentially. The findingsindicated that there was significant difference of post-test score between the students whois givenCollaborative Strategy Readingand students who did not getCollaborativeStrategy Reading. It can be seen from the data analysis by using ANOVA that showedFobserved (10.530) is higher than the critical value of Ftable (at the significant level of 0.05and df = 1/70), namely 3.98. It means that Collaborative Strategy Readinghas significanteffect on students’ reading comprehension in recount text.